BIOLOGICAL DRIED FRUITS EXPORTED FROM GUINEA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The export of fresh and biologically dried fruit is the specialty of the Bio Guinea Company which has its operations in Kiliagbein the Kindia region, some two hours drive north of Conakry. Annual production of 20-25 tonnes of dried bananas,...